2019
DOI: 10.3390/w11050896
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evolution of Seabed Scour Induced by Darrieus-Type Tidal Current Turbine

Abstract: The temporal evolution of seabed scour was investigated to prevent damage around a monopile foundation for Darrieus-type tidal current turbine. Temporal scour depths and profiles at various turbine radius and tip clearances were studied by using the experimental measurements. Experiments were carried out in a purpose-built recirculating water flume associated with 3D printed turbines. The scour hole was developed rapidly in the initial process and grew gradually. The ultimate equilibrium of scour hole was reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The main experimental parameters can be found in Table 2. More details of the experimental setup are elaborated on in the paper in Reference [10].…”
Section: Methodsmentioning
confidence: 99%
“…The main experimental parameters can be found in Table 2. More details of the experimental setup are elaborated on in the paper in Reference [10].…”
Section: Methodsmentioning
confidence: 99%
“…It may vary from time to time. In order to ensure that the TCT can work effectively all the time and avoid the scour effects due to propeller jet velocities [26] [27] and the negative impact of TCT on reducing scour pit depths [28] [29], the TCT will be suspended from a rotating platform, which can rotate around the monopile foundation of the OWT to ensure that the rotor plane of the TCT always faces the direction of the tidal current. The schematic diagram of the proposed technique is shown in Fig.2.…”
Section: Fundamental Mechanism Of the New Countermeasurementioning
confidence: 99%
“…Chen and Lam [5] studied the shadowing effect of a turbine rotor and showed that the velocity of a slipstream is accelerated by about 105%. Previous studies have suggested the presence of tidal turbine effects on seabed scouring [20][21][22][23]. Giles et al [24] showed that flow is suppressed due to blockage and accelerates to balance mass flow and velocity.…”
Section: Introductionmentioning
confidence: 99%